Subversive ceramics - Clare, Claudia (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2016)
"Satire has been used in ceramic production for centuries. Historically, it occurred either as a slogan or proverb written on to the ceramic surface; as pictorial surface imagery; or as a satirical figurine. The use of satire in contemporary ceramics is a rapidly evolving trend, with many artists subverting or otherwise rethinking well known historic forms to make their point. Claudia Clare examines the relationship between ceramics, social politics, and political movements and the way both organisations and individual artists have used these predominantly domestic objects to agitate among the masses or simply express their ideas. 90 colour illustrations of various subversive, satirical and campaigning works illustrate her arguments and enliven debate. Divided into two parts, Subversive Ceramics discusses a selection of historical and contemporary works by artists and makers from twenty-one different countries, from 500BC to the present day"--